2013
DOI: 10.1155/2013/592454
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Healing of Diabetic Wounds by Subcutaneous Administration of Human Umbilical Cord Derived Stem Cells and Their Conditioned Media

Abstract: Objective. Mesenchymal stem cells (MSCs) isolated from the umbilical cord and their conditioned media (CM) can be easily obtained and refined compared with stem cells from other sources. Here, we explore the possibility of the benefits of these cells in healing diabetic wounds. Methodology and Results. Delayed wound healing animal models were established by making a standard wound on the dorsum of eighteen db/db mice, which were divided into three groups with six mice in each: groups I, II, and III received PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 61 publications
3
68
0
1
Order By: Relevance
“…Wounds treated with MSCs in these reports have shown a qualitative improvement regarding histological characteristics, such as superior rete ridge architecture, multi-layered structure, improved dermalepidermal junction and the formation of new skin appendage structures, such as hair follicles and sebaceous glands [120][121][122][123].…”
Section: Msc-related Therapy For Diabetic Woundsmentioning
confidence: 96%
See 2 more Smart Citations
“…Wounds treated with MSCs in these reports have shown a qualitative improvement regarding histological characteristics, such as superior rete ridge architecture, multi-layered structure, improved dermalepidermal junction and the formation of new skin appendage structures, such as hair follicles and sebaceous glands [120][121][122][123].…”
Section: Msc-related Therapy For Diabetic Woundsmentioning
confidence: 96%
“…MSCs have been used to date in treating different skin disorders [20,118,119]; several groups have reported successful wound healing in pre-clinical models of diabetic wounds after the administration of autologous or allogeneic MSCs from different sources [120][121][122][123]. Wounds treated with MSCs in these reports have shown a qualitative improvement regarding histological characteristics, such as superior rete ridge architecture, multi-layered structure, improved dermalepidermal junction and the formation of new skin appendage structures, such as hair follicles and sebaceous glands [120][121][122][123].…”
Section: Msc-related Therapy For Diabetic Woundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, human Wharton's jelly-derived MSC-conditioned media increased the rate of wound closure in mice when delivered in a Matrigel hydrogel, compared to Matrigel alone [ 80 ]. Shrestha et al demonstrated that repeated subcutaneous injection of umbilical cord-derived MSC-conditioned media improved wound healing compared to a single injection of umbilical cord-derived MSCs, suggesting that strategies for sustained delivery of stem cell-conditioned media would be benefi cial in wound therapies [ 110 ].…”
Section: Stem Cell-derived Molecular Therapiesmentioning
confidence: 99%
“…Experiments and clinical trials have highlighted the beneficial effects of MSCs from a variety of sources in dermal repair 133136 . Several studies have recognized the importance of delivering MSCs through a scaffold.…”
Section: Applications Of Mscs In Combination With Elastin-based Bimentioning
confidence: 99%